The development of interactive ski-simulation system by physics-based analysis - Jin, M.; Choi, C.; Ahn, B.; Kim, S.; Chung, K. (The Japanese Journal of Ergonomics, 2013)
In this paper, we have developed a ski-simulation system to obtain more information about the physics-based simulation models using Newton`s second law of motion. We present a real time simulation of ski playing by using the physics-based modeling and verify physics models through field test. We applied these models and parameters by regression analysis to develop interactive ski-simulator. The developed ski-simulator analyzes user`s full body and center of mass using Kinect device in real time and provides feedback about force, velocity and acceleration for user. As a result, through the development of interactive ski-simulator, we accumulated experience and skills based on physics models for development of sports simulator.